In vitro characterization of glycyrol metabolites in human liver microsomes using HR-resolution MS spectrometer coupled with tandem mass spectrometry. (2nd April 2020) - Kim, Younah; Shrestha, Riya; Kim, Sunjoo; Kim, Jeong Ah; Lee, Jaeick; Jeong, Tae Cheon; Kim, Ju-Hyun; Lee, Sangkyu
Abstract: 1. Glycyrol is a coumestan derivative that is isolated from roots of Glycyrrhiza uralensis . Glycyrol exhibits several biological effects, including anti-oxidative and anti-inflammatory effects. 2. Herein, we characterized glycyrol metabolism by cytochrome P450 enzymes (CYPs) and UDP-glucuronosyltransferases (UGTs) using human liver microsomes (HLM), human liver cytosol, human intestinal microsomes, or human recombinant cDNA-expressed CYPs and UGTs. The analysis was conducted using high resolution mass spectroscopy (HR-MS) on a Q Exactive TM HF Hybride Quadrupole-Orbitrap mass spectrometer. 3. NADPH-supplemented HLM generated six glycyrol metabolites (M1–M6) via hydroxylation, oxidation, and hydration; both NADPH- and UDPGA-supplemented liver microsomes generated three glucuronides (M7–M9). Reaction phenotyping revealed that CYP1A2 is the primary enzyme responsible for phase I metabolism, with minor involvement of the CYP3A4/5, CYP2D6, and CYP2E1 enzymes. Glucuronidation of glycyrol was primarily mediated by UGT1A1, UGT1A3, UGT1A9, and UGT2B7. 4. In conclusion, glycyrol undergoes the efficient metabolic hydroxylation and glucuronidation reactions in human liver microsomes, which are predominantly catalyzed by CYP1A2, UGT1A1/3/9, and UGT2B7.